HOUSEHOLD SOLID WASTE MANAGEMENT: COMPOSITIONAL ANALYSIS, STORAGE AND COLLECTION IN THE VITTIN TARGET AREA, TAMALE-GHANA - Denteh, S. N.; Cobbina, S. J.; Adam, W.; Aboka, E. Y. (UDS International Journal of Development, 2018)
Municipal solid waste management has become a complex developmental issue. It has been found not only to affect the environment and public health but it is noted to hinder efforts by several Governments especially in developing countries in the management of the environment. The study aimed at assessing waste management practices at the Vittin Target area, to estimate the quantity and components of waste generated. Questionnaires were distributed to 80 respondents and 80 samples of waste were collected from the various households.Â  Data was analyzed using SPSS software. The study revealed high dependence on private waste collection service providers instead of the usual communal collection systems. About 10% of the respondents practiced waste sorting in the study areas. The rate of solid waste generation was 22.07 kg/day whiles the per capita rate of solid waste generation was 0.33 kg/person/day. The waste was sorted into six fractions of which the highest component was organic, 41.5% by weight. Regression analysis showed a significant positive relationship between generation rate of solid waste and the household size. The results indicate that household size could be an important tool to predict the generation rate of solid waste in the study area, in addition to other social and economic parameters. Based on the findings, there should be regular supervision and monitoring of waste collection by the sanitation institutions to prevent any possible outbreak of diseases such as cholera. Keywords: Municipal solid waste, Waste sorting, Generation rate, Household waste, regression analysis